ARGUMENTATIVE TECHNIQUES: BRIEF ANALYSIS OF OPINION ARTICLES ON DRUG LEGALIZATION - Macêdo Câmara Gracindo, Aline; Linhares de Medeiros Melo, Marina; Bruno Silva Dantas, Francisco; Adeilton de Oliveira Andrade, Emanuel; Lopes Cardoso de Melo, Gislayne (Revista Gênero e Interdisciplinaridade, 2022)
The article analyses, from the perspective of the dialogical theory-analysis of the discourse of the Bakhtin Circle, and the theory of argumentation of Chaim Pelremam, the opinion articles “Legalizing drugs” by federal deputy Jean Wyllys, published in the magazine Carta Capital and “Legalization of drugs” by Dom Odílo P. Scherer, cardinal-archbishop, published in the newspaper O Estado de São Paulo. The objective is to work on the opinion article genre, given that it has a strong argumentative nature, to analyze the aforementioned theories in order to enrich the theoretical debate on argumentative resources. We chose the topic Legalization of drugs because it is a controversial topic that involves several segments and social institutions in its discussion. In order to do so, the dialogic relationships established between the two authors as well as with other social institutions are analyzed, as well as the argumentative techniques used by both to support their points of view, based on the qualitative and interpretive approach of bibliographic research. It appears that the authors dialogue both with each other and with other voices, such as the Supreme Court of Argentina and the church, whether disagreeing or agreeing, in order to affirm their ideological positions when discussing the legalization of drugs. In our conclusive considerations, we highlight the responsive character of the statements, in which an article is constituted as a response to previous positions, while they are opposed, and we also highlight the presence, in both analyzed articles, of Pelremam’s argumentative techniques that were both the arguments based on the structure of the real and the arguments that found the structure of the real.